Bamboo Nanocomposite: Impact of Poly (Ethylene-alt-Maleic Anhydride) and Nanoclay on Physicochemical, Mechanical, and Thermal Properties - Muhammad, Adamu; Sinin, Hamdan; Md. Rezaur, Rahman (NC State University, 2020)
The effects of montmorillonite nanoclay and poly(ethylene-alt-maleic anhydride) via vacuum impregnation technique in relation to the physicochemical, mechanical, and thermal properties of bamboo-reinforced nanocomposites were investigated. The functional groups in the raw bamboo and nanocomposites were identified using Fourier transform infrared spectroscopy. X-ray diffraction plots showed the prominent peak intensity at a diffraction angle of 73° due to the transformation of the amorphous structure to a crystalline structure in the prepared nanocomposite. The morphologies of the raw bamboo and the nanocomposites were compared using scanning electron microscopy analysis. There was an increase in the modulus of elasticity from 7.82 to 19.0 GPa (143%) and a corresponding increase in the modulus of rupture from 68.7 to 121.5 MPa (77%) of the raw bamboo to the nanocomposites, respectively. This increase implied a high increase in the mechanical properties of the developed nanocomposite. Both results from the differential scanning calorimetry and thermogravimetric analysis showed appreciable improvements in the thermal properties of the developed nanocomposite.